IMPLEMENTATION OF ELECTRONIC LICENSING AND INVESTMENT INFORMATION SYSTEM APPLICATION MANAGEMENT (OSS) AT THE ONE-STOP INTEGRATED SERVICE INVESTMENT AND MANPOWER OFFICE OF BARRU REGENCY - Mukmin Muhammad; Hj. Aidah; Aryanti (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
This study aims to determine the Implementation of Electronic Licensing and Investment Information System Application Management (OSS) at the One Stop Integrated Service Investment and Manpower Office of Barru Regency. And To find out the factors that influence the Implementation of Electronic licensing and Investment Imformation System Application Manangement (OSS) at the On Stop Service Investment Office and Barru Regency Manpower. This Research uses descriptive qualitative research type, data sources cousist of primary and secondary data, data colection techniques include observation, interviews, and documentation.The results of this study indicate that the implementation of OSS application management has been implemented in order to improve the quality of licensing better with research indicators according to Edwards, namely communication, resources, disposition and bureaucratic sructure. While the factors that affect the implementation of OSS application management are divided into two. Namely the inhibiting factors which include facilities and infrastructuer, and problematic internet networks and the driving factors which include the ease of issuing business licenses, services is near and can be accessed everywhere.